Precision Logistics as a Strategic Enabler: Lessons from the Past, Demands for the Future - Hrab Daniela-Elena (Scientific Bulletin, 2025)
In the current economic and geo-strategic environment, engaging excessive amount of resources for military operations is perceived as an unacceptable decision. That is why the efficiency and the precision of logistic operations in a permanent volatile context is an objective to be achieved by every commander, in order to be both sustainable and mobile. This paper is designed to highlight the concept of precision logistics, from its original roots to the operational usage insights and future predictions. Moreover, the paper describes some relevant capabilities that might be engaged in developing a precise logistic network, considering the current and future cutting-edge technologies that may enable the processes. To achieve these objectives, relevant literature had been reviewed from the emergence of the concept to the latest theoretical approaches. Moreover, Operation Iraqi Freedom represented a case that was studied for extracting the appropriate details regarding the evolution of precision logistics for military operations, due to the lessons learned 10 years earlier, during Operation Desert Shield/Desert Storm.